Determination of Carbon Steel Dynamic Properties - Jopek, Miroslav (Manufacturing Technology Journal, 2021)
Taylor anvil test is one of the dynamic test method in which we can determine the dependences of strain, strain rate, temperature on flow stress. With this method, we can determine in each cross sec-tion or along axial section of the test specimen conditions under different states of stress, strain, strain rates and subsequent changes in the microstructure of the material. This paper describes the experimental results of the Taylor anvil test (TAT) for TRISTAL carbon steel. The experiment was performed on a TAT test facility in the Laboratory of High Strain Rates at the Faculty of Mechanical Engineering in Brno. For simulation of the mechanical behavior of TRISTAL steel under dynamic load condition was used LS DYNA 3D. This paper also contains the results of the Johnson-Cook constitutive equation for TRISTAL steel. The simulation results are compared with the experimental TAT results.
Keywords: Taylor anvil test; FEM; high strain rates; dynamic load